Herbal Medicine, Gut Microbiota, and COVID-19 - Chen, Ziqi; Lv, Yiwen; Xu, Huachong; Deng, Li (Frontiers in Pharmacology, 2021)
Coronavirus Disease 19 (COVID-19) is a respiratory disease caused by severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2), which has grown to a worldwide pandemic with substantial mortality. The symptoms of COVID-19 range from mild flu-like symptoms, including cough and fever, to life threatening complications. There are still quite a number of patients with COVID-19 showed enteric symptoms including nausea, vomiting, and diarrhea. The gastrointestinal tract may be one of the target organs of SARS-CoV-2. Angiotensin converting enzyme 2 (ACE2) is the main receptor of SARS-CoV-2 virus, which is significantly expressed in intestinal cells. ACE2 links amino acid malnutrition to microbial ecology and intestinal inflammation. Intestinal flora imbalance and endotoxemia may accelerate the progression of COVID-19. Many herbs have demonstrated properties relevant to the treatment of COVID-19, by supporting organs and systems of the body affected by the virus. Herbs can restore the structure of the intestinal flora, which may further modulate the immune function after SARS-CoV-2 infection. Regulation of intestinal flora by herbal medicine may be helpful for the treatment and recovery of the disease. Understanding the role of herbs that regulate intestinal flora in fighting respiratory virus infections and maintaining intestinal flora balance can provide new ideas for preventing and treating COVID-19.